Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.